Sympatric wren-warblers partition acoustic signal space and song perch height. (13th January 2020) - Chitnis, Shivam S; Rajan, Samyuktha; Krishnan, Anand
Abstract: Animals employing acoustic signals, such as birds, must effectively communicate over both background noise and potentially attenuating objects in the environment. To surmount these obstacles, animals evolve species-specific acoustic signals that do not overlap with sources of interference (such as songs of close relatives), and issue these songs from locations that maximize transmission. In multispecies assemblages of birds, the acoustic resource may thus be interspecifically partitioned along multiple axes, including song perch height and signal space. However, very few such studies have focused on open habitats, where differences in sound transmission patterns and limited availability of song perches may drive competition across multiple axes within signal space. Here, we demonstrate acoustic signal space partitioning in four sympatric species of wren-warbler (Cisticolidae, Prinia ), in an Indian dry deciduous scrub-grassland habitat. We found that the breeding songs of the four species partition acoustic signal space, resulting in interspecific community organization. Within each species' signal space, we uncovered different intraspecific patterns in note diversity. Two species partition intraspecific signal space into multiple note types, whereas the other two vary note repetition rate to different extents. Finally, we found that the four species also partition song perch heights, thus exhibiting acoustic niche separation along multiple axes. We hypothesize that divergent song perch heights may be driven by competition for higher singing perches or other ecological factors rather than signal propagation. Acoustic signal partitioning along multiple axes may therefore arise from a combination of diverse ecological processes. Abstract : Our study shows that four sympatric species of wren-warbler in open scrub-grassland habitats exhibit different song note parameters from each other. If we were to represent each song note as a point in a "signal space, " the four species are in different regions or "niches." Finally, the four species also sing from different heights. This "acoustic niche" may enable communication without being drowned out by the songs of other species.